(untitled) (Journal of Architectural Design, 2022)
The article focuses on the development stages of tourism during the Soviet Union, the construction of buildings built for tourist purposes: hotels, tourist centers and complexes, and architectural solutions. Special mention is made of tourist centers and complexes in historic cities, which are the first examples of culture established in the CIS countries during the time of the former Soviet Union. The tourist buildings of Azerbaijan and Turkmenistan were discussed